Independent Curriculum and Behaviorism-Based Learning: Analysis of Reinforcement Effectiveness - Suharni (Yayasan Baru Haji Samsudin, 2025)
This study analyzes the effectiveness of reinforcement in behaviorist-based learning within the Merdeka Curriculum, aimed at enhancing student motivation and engagement for 21st-century learning. Using a quasi- experimental approach with mixed methods, the research involves classroom observations, student questionnaires, and teacher interviews. Findings indicate that positive reinforcement significantly boosts student motivation, particularly when tailored to individual characteristics. However, excessive positive reinforcement risks undermining intrinsic motivation. Negative reinforcement, such as task reduction, can improve student engagement, though it requires careful application to avoid fostering dependency on external support. In inclusive classrooms, reinforcement strategies need to accommodate diverse student needs and abilities. This study suggests that reinforcement within the Merdeka Curriculum should be personalized and balanced, supporting student- centered, independent learning aligned with long-term educational goals